Multiple pathways through which the gut microbiota regulates neuronal mitochondria constitute another possible direction for depression - Zhao, Hongyi; Qiu, Xiongfeng; Wang, Shuyu; Wang, Yi; Xie, Li; Xia, Xiuwen; Li, Weihong (Frontiers in Microbiology, 2025)
As a significant mental health disorder worldwide, the treatment of depression has long faced the challenges of a low treatment rate, significant drug side effects and a high relapse rate. Recent studies have revealed that the gut microbiota and neuronal mitochondrial dysfunction play central roles in the pathogenesis of depression: the gut microbiota influences the course of depression through multiple pathways, including immune regulation, HPA axis modulation and neurotransmitter metabolism. Mitochondrial function serves as a key hub that mediates mood disorders through mechanisms such as defective energy metabolism, impaired neuroplasticity and amplified neuroinflammation. Notably, a bidirectional regulatory network exists between the gut microbiota and mitochondria: the flora metabolite butyrate enhances mitochondrial biosynthesis through activation of the AMPK–PGC1α pathway, whereas reactive oxygen species produced by mitochondria counteract the flora composition by altering the intestinal epithelial microenvironment. In this study, we systematically revealed the potential pathways by which the gut microbiota improves neuronal mitochondrial function by regulating neurotransmitter synthesis, mitochondrial autophagy, and oxidative stress homeostasis and proposed the integration of probiotic supplementation, dietary fiber intervention, and fecal microbial transplantation to remodel the flora–mitochondrial axis, which provides a theoretical basis for the development of novel antidepressant therapies targeting gut–brain interactions.